(untitled) (Latakia University Journal -Basic Sciences Series, 2022)
The change of some hydrochemical parameters (temperature, pH, electrical conductivity) in rainwater was studied. The concentrations of sulfate ion were determined by turbidity method, while the concentrations of (nitrate, nitrite) ions in rainwater were determined using visible spectrophotometry technology at maximum absorption wavelength λmax=407nm, λmax=524nm respectively. Rainwater samples were sampled from four locations distributed within Lattakia city over four sampling rounds that extended from November 2020 to November 2021 at a rate of two rounds each winter. The average pH value was 6.72, which is within the low acidity range, which means that Lattakia city does not be under the influence of acid rain, while the highest values of all ions concentrations were in the mufariq buqa )Alhijrah-Aljawazt( and Sheikhdaher locations, as they represent two vital centers with high human activity and heavy traffic. The nitrate ion concentrations (0.8792-2.7814)ppm were higher than nitrite ion concentrations (0.4851-2.1527)ppm (which is oxidizes to nitrate ion) and also than sulfate ion concentrations (0.8087-1.9685)ppm, which indicates that transport vehicles depend on their fuel at coal extracted from sulfur-poor pits. As a result, it is possible to depend on rainwater to determine the quality of air in Lattakia city, in addition to the possibility of determining the most important influencing factors and working on offering appropriate solutions to reduce pollution, if it exists.